(untitled) (International Journal of Physiotherapy, 2015)
Background: Joint mobilization is an effective intervention for adhesive capsulitis. Scapular mobilization in shoulder adhesive capsulitis is used to decrease intra articular pressure by increasing mobility of the joint capsule and its surrounding soft tissue that results in a reduction of pain and increase range of motion and shoulder function. At the same time the use of mobilization with movement (MWM) for peripheral joints was also used clinically. This technique combines a sustained application of a manual technique ‘gliding’ force to a joint with concurrent physiologic motion of joint, either actively performed by the subject or passively performed by the therapist. So far there is no study which is done on comparison between both of these techniques. The aim of the study is to find out whether the scapular mobilization or mobilization with movement technique improve gleno-humeral range of motion and reduce pain in patients with shoulder adhesive capsulitis. Methods: 50 subjects with adhesive capsulitis were randomly divided in to two groups and one group was treated with mobilization with movement and another group treated with scapular mobilization technique. Each group consist 25 patients. Both groups were given hot packs and pendular exercises as conventional therapy procedures. Treatment was given 5 days a week for 3 weeks. Restricted joint range of motion and severity of pain were measured before and after treatment completion by using goniometer and SPADI pain score respectively. Result: Results of the present study revealed that there was a significant difference in SPADI pain score(%), AROM-GH-Flexion and AROM-GH-External rotation who were treated in group A(MWM) with mean being 44.00, 102.24 and 46.08 respectively compared to group B (SM) with mean being 54.00, 81.00 and 35.84 in 3 weeks. Comparisons between these three parameters used in two treatment techniques were extremely significant (p= 0.000 for all). Conclusion: On the basis of the results, it can be concluded that, the present study provided evidence to support the use of physical therapy regimen for shoulder adhesive capsulitis in the form of mobilization with movement and scapular mobilization in reduction of pain and improvement of glenohumeral range of motion in terms of SPADI pain scale(%) and AROM respectively. In addition results support that mobilization with movement showed better result as compared to scapular mobilization in 3 weeks.